2022
DOI: 10.1177/00494755221076896
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcomes of Diabetic Ketoacidosis during the COVID-19 Pandemic in North India

Abstract: Although recent data have shown a declining trend in mortality in diabetic ketoacidosis (DKA), the outcomes are likely to be different during the coronavirus (COVID-19) pandemic. We conducted a prospective cohort study to evaluate the spectrum and outcomes of adult DKA during the pandemic and document differences in DKA patients with or without COVID-19. A total of 169 patients (mean age 44 years) were admitted at the Emergency Department of PGIMER, Chandigarh (India), from January 2020 to June 2021. The preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
1
0
4
Order By: Relevance
“…A related study reported that 23.1% of DKA patients admitted to a tertiary care centre in North India during the same period were COVID-19 positive. [ 6 ] A prospective study on Indian population reported a significant incidence of new-onset DKA following parenteral glucocorticoids in Type 2 DM (T2DM) patients with COVID-19, especially in those with body mass index <25.56 kg/m 2 , HbA1c% >8.35% and IL-6 levels >50.95 pg/ml at admission. [ 7 ] In a series of 658 patients, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…A related study reported that 23.1% of DKA patients admitted to a tertiary care centre in North India during the same period were COVID-19 positive. [ 6 ] A prospective study on Indian population reported a significant incidence of new-onset DKA following parenteral glucocorticoids in Type 2 DM (T2DM) patients with COVID-19, especially in those with body mass index <25.56 kg/m 2 , HbA1c% >8.35% and IL-6 levels >50.95 pg/ml at admission. [ 7 ] In a series of 658 patients, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Elle est influencée par différents facteurs d'ordre cognitif, comportemental et social (Seydou Moussa et al, 2022). Sa fréquence, comme facteur décompensant du diabète en mode acidocetosique, varie de 16 à 80% selon les études (Belhabib et al, 2018;Gninkoun et al, 2021;Kakoma et al, 2014;Kiran et al, 2022;Oko et al, 2018). Cette disparité dans sa fréquence est sans doute liée à des facteurs individuels mais aussi sociétal variant d'un pays à un autre ou d'une région à une autre.…”
Section: Abstract: Diabetes Ketoacidosis Non-compliance Nigerunclassified
“…S'agissant de la décompensation en mode cétonique d'un patient déjà connu diabétique, plusieurs facteurs pouvant favoriser sa survenue sont décrits dans la littérature tels que l'inobservance thérapeutique, une infection, un accident vasculaire cérébral, une pancréatite, une chirurgie, une insuffisance rénale ou une prise d'alcool (Demir et Seuls les deux facteurs principaux de décompensation ont été identifiés dans notre étude à savoir l'inobservance thérapeutique et la survenue d'une infection L'inobservance thérapeutique est retrouvée chez 83,25% de nos patients. Ce taux est similaire à celui de kiran R et col (Kiran et al, 2022) qui avaient trouvé l'inobservance thérapeutique dans 77,5% des cas. En Inde, Kakoma PK et col (Kakoma et al, 2014) ont trouvé l'inobservance thérapeutique à hauteur de 29,4%.…”
Section: Résultats 21 Caractéristiques Généraux De L'échantillonunclassified
“…Seuls les deux facteurs principaux de décompensation ont été identifiés dans notre étude à savoir l'inobservance thérapeutique et la survenue d'une infection L'inobservance thérapeutique est retrouvé chez 164 patients soit 83,25%. Notre résultat est similaire à celui de kiran R et col (Kiran et al, 2022) qui avaient trouvé l'inobservance thérapeutique dans 77,5% des cas. En Inde, Kakoma PK et col (Kakoma et al, 2014) ont trouvé l'inobservance thérapeutique à hauteur de 29,4%.…”
Section: Résultatsunclassified
“…Elle est influencée par différents facteurs d'ordre cognitif, comportemental et social (Seydou Moussa et al, 2022). Sa fréquence, comme facteur décompensant du diabète en mode acidocetosique, varie de 16 à 80% selon les études (Belhabib et al, 2018;Gninkoun et al, 2021;Kakoma et al, 2014;Kiran et al, 2022;Oko et al, 2018). Cette disparité dans sa fréquence est sans doute liée à des facteurs individuel mais aussi sociétal variant d'un pays à un autre ou d'une région à une autre.…”
Section: Introductionunclassified